Salivary Duct Cyst: A Rare Case Report - Vinayachandran, Divya; Balasubramanian, Saravana Karthikeyan; Siluvai, Sibyl; Lazar, Victor Rakesh; Kalaivani, V.; Mitthra, Suresh; Rajakumar, S. (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Salivary gland non-neoplastic cysts account for 2-5% of all salivary gland lesions and are quite infrequent. Mostly, they are salivary duct cysts or mucoceles. In contrast to a mucocele, which has granulation tissue around it, the salivary duct cyst has epithelium lining it. Salivary duct cysts are rare, reactive ductal lesions of the major salivary glands that are likely caused by obstruction and are lined by true ductal epithelium. It is more common in the oral minor salivary glands and rarely occurs in the major salivary glands, shows a marked predilection for the superficial lobe of the parotid, and represents 10% of all salivary gland cysts. Although they are very rare in children and mostly occur in the fourth decade of life, still the possibility of occurrence should be considered in the differential diagnosis. Neoplastic differentiation of the lining of the salivary duct cyst has been reported. A case of a salivary duct cyst of the left parotid gland, with a review of radiographic and histopathologic features, was reported. The possibility of occurrence in children as well as the probability of malignant changes in the cystic lining should also be considered, making prompt and early diagnosis a priority. Imaging plays a significant role in diagnosing parotid gland duct cysts and ultrasound should be the first modality in its screening.